Magnetic Resonance Imaging With Extracellular Contrast Detects Hepatocellular Carcinoma With Greater Accuracy Than With Gadoxetic Acid or Computed Tomography - Min, Ji Hye; Kim, Jong Man; Kim, Young Kon; Cha, Dong Ik; Kang, Tae Wook; Kim, Honsoul; Choi, Gyu Seong; Choi, Seo Youn; Ahn, Soohyun (Clinical Gastroenterology and Hepatology, 2020)
Background & Aims: Computed tomography (CT) and magnetic resonance imaging (MRI) are used to detect hepatocellular carcinoma (HCC). We performed a prospective study to compare the diagnostic performance of CT, MRI with extracellular contrast agents (ECA-MRI), and MRI with hepatobiliary agents (HBA-MRI) in the detection of HCC using the liver imaging reporting and data system (LI-RADS). Methods: We studied 125 participants (102 men; mean age, 55.3 years) with chronic liver disease who underwent CT, ECA-MRI, or HBA-MRI (with gadoxetic acid) before surgery for a nodule initially detected by ultrasound at a tertiary center in Korea, from November 2016 through February 2019. We collected data on major features and assigned LI-RADS categories (v2018) from CT and MRI examinations. We then compared the diagnostic performance for LR-5 for each modality alone, and in combination. Results: In total, 163 observations (124 HCCs, 13 non-HCC malignancies, and 26 benign lesions; mean size, 20.7 mm) were identified. ECA-MRI detected HCC with 83.1% sensitivity and 86.6% accuracy, compared to 64.4% sensitivity and 71.8% accuracy for CT (P <.001) and 71.2% sensitivity (P =.005) and 76.5% accuracy for HBA-MRI (P =.005); all technologies detected HCC with 97.4% specificity. Adding CT to either ECA-MRI (89.2% sensitivity, 91.4% accuracy; both P <.05) or HBA-MRI (82.8% sensitivity, 86.5% accuracy; both P <.05) significantly increased its diagnostic performance in detection of HCC compared with the MRI technologies alone. ECA-MRI identified arterial phase hyperenhancement in a significantly higher proportion of patients (97.6%) than CT (81.5%; P <.001) or HBA-MRI (89.5%; P =.002). ECA-MRI identified non-peripheral washout in 79.8% of patients, vs 74.2% of patients for CT and 73.4% of patients for HBA-MRI (differences not significant). ECA-MRI identified enhancing capsules in 85.5% of patients, vs 33.9% for CT (P <.001) and 41.4% for HBA-MRI (P <.001). Conclusion: In a prospective study of patients with chronic liver disease and a nodule detected by ultrasound, ECA-MRI detected HCC with higher levels of sensitivity and accuracy than CT or HBA-MRI, based on LI-RADS. Diagnostic performance was best when CT was used in combination with MRI compared with MRI alone.
Keywords: Carcinoma, Hepatocellular; Contrast Media; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies; Retrospective Studies; Sensitivity and Specificity; Tomography, X-Ray Computed; Comparison; Diagnosis; Early Detection; Liver Cancer